The Influence of Promotional Mix on Decision Making to Purchase Oppo Brand Cell Phones in Medan City - Susanto; Saskia; Rini Indahwati (Outline Journal of Economic Studies, 2022)
This study aims to determine the effect of the Promotional Mix on decision making of buying OPPO cellular phones in the city of Medan. This study uses a quantitative descriptive approach because it uses a survey (Questionnaire), while the nature of the research is explanatory research. This research was conducted by researching and collecting data as the author's analysis material, which was carried out in 15 sub-districts carried out from April 2022 to June 2022 using Proportionate Stratified Random Sampling, so that a sample of 205 respondents was obtained. The results of the research analysis show that Advertising, Direct Selling, Interactive Selling, Personal Selling, Sales Promotion and Public Relations have a positive and significant influence on Decision Making of using OPPO cellular phones. The results showed that Advertising, Direct Selling, Interactive, Personal Selling, Sales Promotion, and Public Relations simultaneously had a positive and significant effect on Decision Making of buying OPPO Mobile Phones in Medan City.